Variation in Ralstonia solanacearum Isolated from Brinjal Plants in West Bengal - Mondal, B.; Bhattacharya, I.; sarkar, A.; Khatua, D. C. (International Journal of Bio-resource and Stress Management, 2011)
Bacterial wilt caused by Ralstonia solanacearum (Smith) Yabuuchi et al. (=Pseudomonas solanacearum E.F.Smith) is prevalent in West Bengal infecting brinjal, tomato, potato, tobacco and chilli every year and causing extensive damage to crops. Affected brinjal plants showed leaf drooping, followed by complete or partial wilting. Browning of inner tissues of the vascular bundle can be observed in infected plants. Isolates of R. solanacearum collected from different geographical and environmental milieu did not show any type of variation with respect to their physico-biochemical characteristics of the pathogen. However, regional level variations in aggressiveness of R. solanacearum were found among the isolates collected from infected brinjal plants.